Taxonomic revision of Joannesia (Euphorbiaceae), an endemic genus of Brazil with two geographically disjunct species - Külkamp, Josimar; Fraga, Claudio N.; Iganci, João R.v. (Phytotaxa, 2020)
Joannesia is a genus of Euphorbiaceae composed of two endemics species to Brazil, one occurring in the Amazonia and another mainly on the Atlantic Forest. The genus was formally described by Frei José Mariano da Conceição Vellozo in 1798 but this taxon had been already mentioned by Willem Pies and Georg Marcgrave in 1648 under a different name. The genus has been greatly altered throughout the history due to other names described and adopted by subsequent researchers. Herbarium collections and scientific bibliography were consulted. Specimens collected during field expeditions were deposited in the RB herbarium. A taxonomic review for the species of Joannesia is presented, along with an identification key with reproductive and vegetative characters, updated geographic distribution for each species, as well as typifications according to the ICN and notes on the species.